Prolegomeni alle origini del Secolo russo: un dodecalogo a mo’ di vademecum - Lenzi, Massimo (Mimesis Journal, 2017)
Why Russian theatre and drama, starting from the rearmost ranks in general critical appreciation, between 1898 and 1912 quickly rose to play the role of the most advanced aesthetic culture in Western – lato sensu – civilization, so much that the twentieth century has been considered nearly as the “Russian Century” insofar as what concerns theatre? This short essay outlines twelve points, equally divided up between historical and theoretical contexts, identifying as many hypothetical “research proto- cols”: in the author’s opinion possible answers may emerge by correlating each one’s provisional results, which answers may appear as less impromptu, more grounded and consistent than those theatre studies gave (usually only by implication) until now when dealing with that season in Russian theatrical culture.